5th International Conference OTEH 2012 - defense technology (Proceedings review) - Đurković, Vlado Petar (Vojnotehnički glasnik / Military Technical Courier, 2013)
This article gives an overview of all papers and events at the Fifth International ScientificConference on Defense Technologies OTEH 2012 held in Belgrade, in the Military Technical Institute (VTI), from 18th to 19th September 2012. The paper review presents the Conference Sections by subjects and guest-lectureres as well as the institutions of all authors who actively participated at the Conference. About the Conference The Fifth International Scientific Conference on Defense Technologies OTEH 2012 was held in Belgrade in the Military Technical Institute in Žarkovo, from 18th to 19thSeptember 2012.. The Conference program was organized in two plenary sessions and a working part which took place in four halls. In the plenary session, two key lectures were held by eminent experts from abroad. The first lecture entitled „An adaptive remeshing technique for 3D crack growth simulations”, was given by Dr Vincent Chiaruttini (ONERA Institute, Paris, France). The second one, „New Technologies for Advanced Defence Systems”, was held by Dr Filippo Neri (Virtualabs Company, Rome, Italy). Fifteen sessions were organised at the Conference. The authors presented their works in open discussions answering questions from the audience. The average number of attendees at each session was about 40. The papers were sorted by topic areas: • Aerodynamics and flight dynamics: 12 papers • Aircraft: 23 papers • Weapon systems, ammunition, energy materials, combat vehicles: 29 papers • Integrated sensor systems and robotic systems: 16 papers • Telecommunication and information systems: 18 papers • Materials and technologies: 34 papers • Quality, standardization, metrology, maintenance and exploitation: 11 papers Out of 163 submitted papers for this Conference, 145 papers were accepted and distributed in an electronic form on CDs to the present authors, co-authors, guests and invitees to the Conference. The number of participants with authors and co-authors was impressive - 243. The authors (either of their own or plenary papers) from 15 countries were present at the Conference. It should be noted that at this conference, unlike the previous one also held in the VTI, Belgrade, in 2011, there was a significantly higher number of younger researchers. There was a general impression that many reseach results communicated at the Conference deserved to be published in reference journals on the SCR list. A number of papers from this Conference will be considered for publication in the Scientific Technical Review. It should be noted that the MO-VTI organizing committee largely contributed to the Conference to be evaluated as a well-organized event. From a total number of papers (145), there were 32 (or 22.06% ) from abroad. Once again, the Conference justified the purpose of this type of conferences. The other works of authors and co-authors were from the following institutions in Serbia: • The Ministry of Education and Science and Technological Development, • Military Technical Institute (VTI), Military Academy (MA), the Army of Serbia (SAF), the Ministry of Defence (MOD), Department of Defense Technology (MDT), University of Defence (UD) Military Institution Dedinje, Military Archives, Technical Test Center (TTC), Technical Overhaul Institute Čačak (TRZ), the Central Logistics Base, Institute of Strategic Studies, Criminal Police College, • GOŠA Institute, Institute of Engineering, • Faculties of Mathematics, Mechanical Engineering, Electrical Engineering, Metropolitan University, Faculty of Technology and metallurgy, College of Project Management, • UTVA Aircraft Industry Pančevo, Intel Communications, IHATEM, Vlata com, Iritel, Peripolis-Electronics, Computer Engineering, Thermo Electric, HK Krušik Valjevo. Conclusion The Conference had a truly international character. As in previous years, the participation of the Army of Serbia in this important event is fully justified, and the goal is reached. In addition to the communication of the research results, there was a fruitful discussion in which the problems were reviewed, opinions and experiences exchanged and possibilities to solve presented problems discussed. It was again confirmed that communicating work at such events with the participation of scientists and relevant institutions from the country and abroad certainly has a positive impact on the scientific and professional level of work in the Army. It also has a positive impact on professional and scientific training of researchers in experimental centers and institutes as well as teachers, thus raising the quality of teaching in undergraduate and postgraduate studies at the Military Academy. It can be concluded that the cooperation of the Army with the members of other institutions in solving and researching problems of organizations and scientific-technical approach confirms the openness of the Army for the involvement of other individuals and institutions in solving problems in the field of defense as well as the willingness and ability of the members of the defense system to engage in solving problems in civil institutions.